Extraction of alpha-tocopherol from corn - Nor Hazlila, Basiran (2006)
Corn (Zea mays) is fruit that have high concentration of Alpha-tocopherol (Vitamin E) in their composition. Alpha-tocopheol is an antioxidant that was used in industries especially pharmaceutical product as a stabilizer, plastic industries, technical oil, and greases. Before extract the Alpha-tocopherol, the corn juice must be blend by using blender to liquefy it. The corn must be manually cut from cob and blend it using blender then the juice was being filter. A High-performance liquid chromatographic (HPLC) method was used to determine the Alpha-tocopherol level in corn. The mixture of acetonitrile/methanol/dicloromethane (60:38:2, v/v) was used as mobile phase at a flow rate of 0.2 mL min1 at temperature 300C. alpha-tocopherol must be determine between 2-5 minute peak. For the result, the peaks for standard are between 2-3 minute. As a result, the peak did not get because of there are some problem at the column. This research finally did not obtain the objective of the research.